Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/w9060418
|View full text |Cite
|
Sign up to set email alerts
|

Using Modeling Tools to Better Understand Permafrost Hydrology

Abstract: Modification of the hydrological cycle and, subsequently, of other global cycles is expected in Arctic watersheds owing to global change. Future climate scenarios imply widespread permafrost degradation caused by an increase in air temperature, and the expected effect on permafrost hydrology is immense. This study aims at analyzing, and quantifying the daily water transfer in the largest Arctic river system, the Yenisei River in central Siberia, Russia, partially underlain by permafrost. The semi-distributed S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 62 publications
(94 reference statements)
1
25
0
1
Order By: Relevance
“…6-Fabre et al [30] studied the effect of permafrost degradation as a result of increasing temperature in the largest Arctic river system: the Yenisei River in central Siberia, Russia. Once the climate data and soil conditions were adapted to a permafrost watershed, the calibration results showed SWAT was able to estimate water fluxes at a daily time step, especially during unfrozen periods.…”
Section: Appendix Amentioning
confidence: 99%
“…6-Fabre et al [30] studied the effect of permafrost degradation as a result of increasing temperature in the largest Arctic river system: the Yenisei River in central Siberia, Russia. Once the climate data and soil conditions were adapted to a permafrost watershed, the calibration results showed SWAT was able to estimate water fluxes at a daily time step, especially during unfrozen periods.…”
Section: Appendix Amentioning
confidence: 99%
“…Importantly, both the SWAT model and the ArcSWAT interface are openesource and free, allowing reproducibility of the results once the input data are welledocumented (Olivera et al, 2006). The SWAT model has already been tested in Arctic systems (Krysanova and White, 2015;Hülsmann et al, 2015) and revealed its capability to accurately represent permafrost hydrology (Fabre et al, 2017). Theory and details of hydrological processes inte grated in SWAT model are available online in the SWAT docu mentation (http://swatmodel.tamu.edu/).…”
Section: Study Areamentioning
confidence: 99%
“…Numerous models have been used in past researches to simulate permafrost hydrology. (Fabre et al, 2017). The TOPMODEL, a surface runoff model, has shown its limits for small to the largest Arctic watersheds by omitting lateral and groundwater flow (Stieglitz et al, 2003;Finney et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrological modelling strategies accounting for permafrost-specific processes should be developed or further enhanced for their better representation. The most promising approaches include: (1) Coupled water and heat balance models of various dimension and complexity, e.g., the 'zero-dimensional' model of Boike et al [22], PFLOTRAN [96], SUTRA 3.0 (aka SUTRA-ice) [97] and permaFOAM [98], to mention but a few; (2) an explicit two-dimensional heat transfer model with phase transitions, where water and heat fluxes are decoupled [99]; and (3) semi-distributed models with a simplistic permafrost description as an impermeable layer, and no heat transfer module [100,101].…”
Section: Future Progress In Permafrost Hydrology Domainmentioning
confidence: 99%